Aluminum anode oxide film secondary self-assembly hydrophobic membrane sealing concentrated solution and sealing method
By using aluminum anodized film secondary self-assembled hydrophobic film sealing concentrate at room temperature for secondary sealing, the problems of poor quality of lithium salt sealing at room temperature and poor surface state are solved, and efficient pore sealing and pollution resistance are achieved Improve and achieve the closed effect of national standards.
Patent Information
- Application Number
- CN202411352727.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the sealing quality of lithium salt at room temperature does not meet the standards, the surface state is poor, and the fluorine-containing ion solution is prone to turbidity and aging, and the surface of the oxide film is prone to corrosion and blackness, affecting the sealing effect.
Provided is an aluminum anodized film secondary self-assembled hydrophobic film sealing concentrate solution, containing 1% to 5% of sulfonate anionic surfactant, 0.1% to 0.5% of blocking accelerator, 2% to 6% of inorganic salt , 0-0.03% fungicide and 0-0.05% defoaming agent are adjusted to perform secondary sealing treatment by adjusting the working fluid with a pH of 4-7 to form a self-assembled hydrophobic film to improve pore sealing and pollution resistance.
At room temperature, the sealing quality of lithium salts is significantly improved, the sealing degree and pollution resistance are blocked, and the weight loss of nitric acid is reached by phosphate-chromic acid. The surface is uniformly hydrophobic, no sealing gray, smooth, close to traditional fluorination. Nickel enclosed level.
Smart Images

Figure CN119265667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aluminum alloy surface treatment, and in particular relates to an aluminum anodized film secondary self-assembled hydrophobic film sealing concentrated solution and a sealing method. Background Art
[0002] Aluminum or aluminum alloy is subjected to electrochemical oxidation treatment to obtain an anodic oxide film, which is a porous film. Post-sealing treatment is the key process technology for the engineering application of aluminum anodized film. From the initial steam and boiling water sealing to medium-temperature and room-temperature sealing containing heavy metal nickel, and then to nickel-free medium-temperature and room-temperature sealing, the sealing technology of aluminum alloy anodized film has developed in the direction of environmental protection and energy saving.
[0003] The environmentally friendly and energy-saving sealing process containing light metal lithium salts has been applied in industrial production, but the room temperature lithium salt sealing process needs to be further improved. The main reason is that the sealing quality at room temperature (25℃~30℃) needs to be improved (it can only meet the sealing of some low-grade materials); the arbitration test results of the phosphochromic acid weight loss method are generally 50mg / dm 2 Above, significantly higher than the national standard of 30mg / dm 2 ; The blue ink pollution resistance performance online test has obvious residual marks. In addition, due to the high concentration of fluoride ions in the bath liquid, at a closed temperature above 30°C, the bath liquid is prone to turbidity and aging, the oxide film surface is prone to dusting during large-scale production, and the thin oxide film is prone to corrosion and blackening. Therefore, the current lithium salt sealing cannot be stably produced and applied at 25-30°C like the room temperature nickel fluoride process.
[0004] At a medium temperature of 60-70℃, most nickel-free sealing can use organic surfactants or anionic surfactants as promoters, which have a good sealing effect on the oxide film. However, at room temperature, the promoter F ions must be added to complete the sealing process of the oxide film. In a solution containing fluoride ions, the addition of organic active substances generally cannot play a composite synergistic role in the sealing of the anodic oxide film. Because according to the mechanism of promoting sealing, the F ion has a small radius and high activity, and it is easy to first adsorb into the membrane interface and pores, change the interfacial charge state of the oxide film surface, make the surface or the inner wall of the pore negatively charged, and through the electrical adsorption of cations (Li, Ni), at a suitable pH, hydroxides and fluorine-containing complexes are generated and deposited in the pores, thereby sealing the oxide film; if a series of organic promoters suitable for use under medium temperature conditions are continued to be added, they will compete with the F ions for adsorption, affecting the adsorption of the F ions, and then affecting the participation of the F ions in promoting the sealing process of the oxide film, which may have a negative impact on the final sealing quality. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide an aluminum anodized film secondary self-assembled hydrophobic film sealing concentrate and a sealing method, and solve the technical problems of substandard quality and poor surface state of room temperature lithium salt sealing in the prior art.
[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In the first aspect, the present invention provides an aluminum anodized film secondary self-assembled hydrophobic film sealing concentrate, which comprises the following components by mass percentage: 1% to 5% of a sulfonate anion surfactant, 0.1% to 0.5% of a sealing promoter, 2% to 6% of an inorganic salt, 0 to 0.03% of a bactericide, 0 to 0.05% of a defoaming agent, and the remainder is pure water.
[0007] In a second aspect, the present invention provides a method for secondary sealing of anodized aluminum film, comprising the following steps: The above-mentioned secondary self-assembled hydrophobic membrane sealing concentrated solution is diluted with water and the pH value is adjusted to 4-7 to obtain a working solution; the aluminum anodized film sample is cleaned after nickel-free sealing treatment to obtain a primary sealing sample; the primary sealing sample is immersed in the working solution, and a secondary sealing treatment is performed, and finally the secondary sealing of the aluminum anodized film is completed by drying.
[0008] Compared with the prior art, the beneficial effects of the present invention include: The sealing concentrate of the present invention is used as a normal temperature (20°C-30°C) nickel-free and fluorine-free sealing solution, which can further improve the normal temperature lithium salt sealing quality, form a secondary self-assembled hydrophobic sealing film on the anodic oxide film after the first lithium salt sealing solution is sealed, improve the sealing degree and pollution resistance of the anodic oxide film, and make the weight loss data of nitric acid pre-immersion phosphorus-chromic acid after the secondary sealing reach the national standard of 30mg / dm 2 The following results show that the blue ink adsorption capacity loss detection on the oxidation line is completely free of pollution marks; the closed surface state of the anodized film is improved, so that the surface of the anodized film is uniformly hydrophobic, free of closed ash and smooth to the touch. The closed concentrate and the closed method of the present invention can promote the sealing of the aluminum anodized film to truly turn to a low-temperature heavy metal-free sealing process, and the sealing quality basically reaches the level of the traditional nickel fluoride-containing sealing. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a test diagram of the wettability of the aluminum alloy test piece surface obtained by the secondary sealing process in Example 5; Figure 2 This is a test diagram of the surface wettability of a single-sealed aluminum alloy test piece obtained by a single lithium salt sealing process in Comparative Example 1; Figure 3 The graph showing the loss of adsorption capacity of the once-sealed aluminum alloy test piece obtained by the lithium salt sealing treatment in Comparative Example 1, wherein (a) is after the blue ink is applied, and (b) is after the blue ink is washed with running water; Figure 4 The adsorption capacity loss detection diagram of the secondary sealed aluminum alloy test piece obtained by placing the once sealed aluminum alloy test piece of comparative example 1 into the working solution of example 5 for secondary sealing treatment, wherein (a) is after applying blue ink, and (b) is after washing the blue ink with running water. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0011] The sealing quality of the room temperature lithium salt sealing process needs to be improved, and it is easy to have problems such as turbidity and aging of the tank liquid, graying of the oxide film surface in large-scale production, and corrosion and blackening of the thin oxide film. In view of the problems that still exist in the room temperature lithium salt sealing and the characteristics of fluorine in its sealing liquid, the present invention provides a secondary self-assembled hydrophobic film sealing concentrate and a sealing method for aluminum anodized film, which utilizes the characteristics of self-adsorbed organic molecular film on the surface of the nanoporous oxide film, and uses a self-assembled hydrophobic film sealing concentrate as a secondary sealing working liquid raw material, and performs secondary sealing on the anodized film at room temperature to form an organic molecular layer film to improve the sealing degree and protection ability of the oxide film, so that the sealing quality of the overall oxide film is improved, thereby meeting the sealing quality requirements of the national standard. And the secondary sealing process adopted in the present invention avoids the traditional direct addition of organic surfactants to the fluorine-containing room temperature sealing liquid, which will produce competition and affect the defects of the original F ion promoting sealing.
[0012] Among them, self-assembled membrane refers to the spontaneous adsorption of organic molecules on the solid surface through electrical properties, van der Waals forces or bonding methods to form a two-dimensional or three-dimensional orderly molecular layer with a certain thickness. Self-assembled membrane technology is a surface modification technology with a wide range of applications in metal surface protection, nanocrystalline films and biomedical drug delivery.
[0013] The present invention adopts the electrical adsorption design of the charged polar molecules in the self-assembled hydrophobic membrane-enclosed concentrated solution and the easily adsorbed nanoporous surface with opposite charge, and can self-assemble at room temperature to form a dense single-molecule hydrophobic membrane with the hydrophobic base facing outward, which can significantly improve the protective function of the previous surface treatment.
[0014] In the first aspect, the present invention provides an aluminum anodized film secondary self-assembled hydrophobic film sealing concentrate, which comprises the following components by mass percentage: 1% to 5% of a sulfonate anion surfactant, 0.1% to 0.5% of a sealing promoter, 2% to 6% of an inorganic salt, 0 to 0.03% of a bactericide, 0 to 0.05% of a defoaming agent, and the remainder is pure water.
[0015] The material of the aluminum anode in the present invention may specifically include aluminum or aluminum alloy.
[0016] The secondary self-assembled hydrophobic membrane closed concentrated solution is obtained by sequentially mixing a sulfonate anionic surfactant, a closed accelerator, an inorganic salt, a bactericide and a defoamer with pure water.
[0017] Preferably, the following components are included by mass percentage: 3% to 5% of sulfonate anionic surfactant, 0.3% to 0.5% of sealing promoter, 4% to 6% of inorganic salt, 0 to 0.03% of bactericide, 0 to 0.05% of defoamer, and the balance is pure water.
[0018] Preferably, the sulfonate anionic surfactant comprises C 10 ~C 16 Alkyl sulfonate, C 10 ~C 16 Alkylbenzene sulfonate, C 10 ~C 16 One or more of alkyl diphenyl ether disulfonates, methylene bis naphthalene disulfonates, α-olefin sulfonates, petroleum sulfonates, lignin sulfonates and naphthalenesulfonic acid formaldehyde condensates.
[0019] Further preferably, the sulfonate anionic surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, sodium methylene dinaphthalene disulfonate, sodium lignin sulfonate, potassium lignin sulfonate and naphthalenesulfonic acid formaldehyde condensate.
[0020] Preferably, the blocking promoter includes one or more non-ionic surfactants such as C4-C8 fatty alcohols, C4-C8 fatty acids, fatty alcohol polyoxyethylene ethers, fatty acid polyoxyethylene ethers, polyoxyethylene sorbitan fatty acid esters, etc.
[0021] Further preferably, the blocking promoter includes one or more of butanol, amyl alcohol, isopentanol, octanol, succinic acid, adipic acid, JFC penetrant, FMEE penetrant (fatty acid methyl ester ethoxylate), Tween 20, Tween 40 and Tween 60.
[0022] Preferably, the inorganic salt is an alkali metal or alkaline earth metal inorganic salt, specifically including one or more of water-soluble salts of sodium, potassium, lithium, magnesium and calcium.
[0023] Preferably, the inorganic salt includes one or more of sodium sulfate, sodium acetate, magnesium acetate, magnesium sulfate, calcium acetate and lithium acetate.
[0024] Preferably, the bactericide includes a fatty amine polyoxyethylene ether surfactant, and the defoamer is a polyether defoamer. Among them, the fatty amine polyoxyethylene ether surfactant is cationic under acidic conditions and has a certain bactericidal effect.
[0025] In a second aspect, the present invention provides a method for secondary sealing of anodized aluminum film, comprising the following steps: The secondary self-assembled hydrophobic membrane sealing concentrated solution is diluted with water and the pH value is adjusted to 4-7 to obtain a working solution; The aluminum anodized film sample was cleaned after being treated with nickel-free sealing to obtain a primary sealed sample; The primary sealed sample is immersed in the working solution, and then subjected to secondary sealing treatment. Finally, the secondary sealing of the aluminum anodized film is completed by drying.
[0026] Preferably, the nickel-free sealing treatment is carried out by immersing the aluminum anodized film sample in a lithium salt sealer, the sealing temperature is 25°C to 30°C, and the sealing speed is 1.5 to 2 min / μm; the components of the lithium salt sealer include: lithium ions 0.6 to 1.1 g / L, fluoride ions 0.3 to 0.6 g / L, tungstate 0.5 to 1 g / L, and the pH value of the lithium salt sealer is 8.5 to 9.0; cleaning includes water washing and pure water washing with a conductivity of less than 20 μs / cm.
[0027] Preferably, the working solution is obtained by mixing and diluting the secondary self-assembled hydrophobic membrane sealing concentrate and pure water at a mass ratio of 1: (8-10) and adjusting the pH value to 4.5-5.5.
[0028] Preferably, the secondary sealing treatment is an immersion treatment at 22°C to 30°C for 5 to 15 minutes.
[0029] Preferably, the drying is natural air drying or hot air drying.
[0030] The main mechanism of action and advantages of the present invention: (1) According to the principle of isoelectric point electrical adsorption, under acidic conditions (pH less than 7), the surface of the aluminum anodic oxide film (Al2O3 with nanopores) is positively charged and can electrically adsorb negatively charged organic molecules. Anionic surfactants are organic molecules with negatively charged head groups and hydrophobic tail groups. Acid and alkali resistant sulfonate anionic surfactants are the best type of self-assembling organic substances. The longer the hydrophobic tail group, the more hydrophobic groups such as CH3, CF3, and Si are contained, the stronger the power to "escape" from water, and the faster and more stable the self-assembly process with reduced entropy of the system. At the same time, considering the water solubility and stability issues, the present invention uses single or multiple sulfonic acid anionic surfactants with multi-branched tail groups as the organic molecular main agent of the self-assembled hydrophobic film.
[0031] (2) The metal cations of the inorganic salts compress the diffuse double layer of the negatively charged head groups of the sulfonate anionic surfactants, making the charge density of the charged head groups larger and the hydrophobic chain organic molecules adsorbed on the surface denser and more firmly.
[0032] (3) Sealing promoters include water-soluble long-chain fatty alcohols or acids, fatty alcohol hydrophobic nonionic surfactants, etc., which can "insert" into the adsorption layer of sulfonate anionic surfactants through the hydrophobicity of carbon chains, the dipole electrical effects of alcohols and acids, and the hydrogen bonding of polyoxyethylene chains, increase the surface hydrophobic chain density, weaken the electrostatic repulsion of the charged head groups, and make the self-assembled adsorption layer more stable. At the same time, it can also reduce the micelle concentration cmc and usage of sulfonate anionic surfactants.
[0033] (4) The self-assembled hydrophobic membrane-enclosed concentrated liquid of the present invention is an organic liquid. The wastewater tank liquid generated after its use can easily become a culture medium for bacterial reproduction. In addition, the impact of the tank liquid will produce foam, affecting normal production. Therefore, defoaming agents and bactericides can be added in appropriate amounts as needed.
[0034] (5) The present invention designs a self-assembled adsorption layer based on electrical adsorption, in which the intrinsic isoelectric point parameter of the substrate surface is crucial. When the solution pH is lower than the isoelectric point of the substrate, the substrate surface is positively charged; otherwise, it is negatively charged, and the greater the difference, the more charged the substrate surface is, and the easier it is to adsorb organic molecules with opposite charges to form a dense adsorption film. The surface of the anodic oxide film (Al2O3 with nanopores) of aluminum and aluminum alloy is a surface layer with aluminum oxide as the main component, and its isoelectric point in aqueous solution is about 9. Therefore, according to the isoelectric point principle and the faster corrosion reaction of aluminum oxide film in alkaline environment, the pH of the self-assembled hydrophobic film sealing concentrate of the present invention should be adjusted to an acidic condition with a small pH, and the smaller the pH, the easier it is to form an adsorption film. However, the pH should also take into account the limitation of the corrosion reaction of the substrate in the aqueous solution. Therefore, the present invention preferably has a pH value of neutral to slightly acidic for the secondary sealing treatment working solution, and more preferably a pH value of 4.5 to 5.5; at the same time, molecular adsorption is an exothermic process, so the present invention can self-assemble to form a hydrophobic film at room temperature.
[0035] Therefore, the sealing concentrate of the present invention can be used as a room temperature sealing liquid to form a secondary self-assembled hydrophobic sealing film on the anodic oxide film after the first lithium salt sealing, thereby improving the sealing degree and pollution resistance of the anodic oxide film. At a room temperature of 25-30°C, the weight loss test of phosphorus-chromic acid can reach the national standard of 30mg / dm 2 And below, and after sealing, the surface of the aluminum material feels smooth and has uniform color.
[0036] The self-assembled hydrophobic film sealing concentrated solution of the present invention can form a good self-assembled hydrophobic film effect on a suitable pre-treated metal surface, preferably has a good self-assembled hydrophobic film effect on an aluminum alloy anodized film.
[0037] The present invention is further described in detail below through specific examples.
[0038] Example 1 A secondary self-assembled hydrophobic membrane sealing concentrate, comprising the following components by mass percentage: Sodium dodecyl sulfate 4%; Butanol 0.5%; Sodium sulfate 5%; Pure water balance.
[0039] A secondary sealing method for anodized aluminum film comprises the following steps: (1) Aluminum alloy anodizing treatment: Anodizing treatment is common sulfuric acid anodizing of 6063 aluminum alloy at 1.2A / dm 2 , oxidized for 27 minutes, washed twice with water and then washed with pure water to obtain an aluminum anodized film sample with a film thickness of about 10 microns.
[0040] (2) Lithium salt nickel-free sealing at room temperature: The aluminum anodized film sample is immersed in a lithium salt sealant for nickel-free sealing treatment, and then washed with water and pure water to obtain a once-sealed aluminum alloy; the components of the lithium salt sealant and the process conditions for the nickel-free sealing treatment are: lithium acetate dihydrate 9 g / L, ammonium bifluoride 0.9 g / L, sodium tungstate 0.6 g / L, pH 8.8, temperature 26 °C, and time 12 min.
[0041] (3) The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 4.5 with 2% glacial acetic acid to obtain a working solution; the primary sealed aluminum alloy was immersed in the working solution for secondary sealing treatment at a temperature of 26°C and an immersion time of 10 min; finally, after drying, the secondary sealing of the aluminum anodized film was completed.
[0042] Example 2 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Sodium lignin sulfonate 2.5%; Sodium dodecylbenzenesulfonate 1.5%; Isoamyl alcohol 0.4%; Magnesium sulfate 5%; Pure water balance.
[0043] The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 5.5 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 25°C for 10 minutes.
[0044] Example 3 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Potassium lignin sulfonate 4.0%; Sodium dodecyl diphenyl ether disulfonate 1.0%; Octanol 0.3%; Magnesium acetate 5%; Pure water balance.
[0045] The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 5.0 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 26°C for 10 minutes.
[0046] Example 4 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Sodium methylene dinaphthalene disulfonate 2.5%; Sodium dodecylbenzenesulfonate 1.5%; Succinic acid 0.4%; Magnesium sulfate 5%; Pure water balance.
[0047] The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 5.0 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 26°C for 10 minutes.
[0048] Example 5 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Naphthalenesulfonic acid formaldehyde condensate 3%; Potassium lignin sulfonate 1.5%; JFC penetrant 0.3%; Magnesium sulfate 2%; Sodium sulfate 2%; Fatty amine polyoxyethylene ether (AC-1812) 0.02%; Pure water balance.
[0049] The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 5.0 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 26°C for 10 minutes.
[0050] The wettability test was conducted by dripping water on the aluminum alloy test piece obtained by the secondary sealing process in Example 5. The results are as follows: Figure 1 As shown, the results show that the surface of the aluminum alloy specimen obtained by the secondary sealing process is hydrophobic (the contact angle is greater than 90°).
[0051] Example 6 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Naphthalenesulfonic acid formaldehyde condensate 3%; Potassium lignin sulfonate 1.5%; FMEE penetrant 0.4%; Magnesium acetate 2%; Calcium acetate 2%; Polyether defoamer 0.01%; Pure water balance.
[0052] The secondary self-assembled hydrophobic membrane sealing concentrate was diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 6.0 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 26°C for 12 minutes.
[0053] Example 7 The only difference from Example 1 is that the working solution and process conditions used in the secondary sealing treatment in step (3) are different, and the other steps and conditions are the same as those in Example 1; wherein the secondary self-assembled hydrophobic membrane sealing concentrate specifically includes: Naphthalenesulfonic acid formaldehyde condensate 4%; Tween 200.2%; Tween 400.2%; Magnesium acetate 2%; Lithium acetate 2%; Fatty amine polyoxyethylene ether (AC-1812) 0.02%; Polyether defoamer 0.01%; Pure water balance.
[0054] The secondary self-assembled hydrophobic membrane sealing concentrate was mixed and diluted with pure water at a mass ratio of 1:9, and the pH value was adjusted to 5.0 with 2% glacial acetic acid to obtain a working solution; the secondary sealing treatment conditions were: soaking at 26°C for 10 minutes.
[0055] Comparative Example 1 The only difference from Example 5 is that step (3) of Example 5 is removed, that is, a lithium salt sealing agent is used for a sealing treatment, and the other steps and conditions are the same as those of Example 5.
[0056] The wettability test was performed by dripping water on the once sealed aluminum alloy test piece obtained by the lithium salt sealing process in Comparative Example 1. The results are as follows: Figure 2 As shown, the results show that the surface of the once-sealed aluminum alloy specimen obtained by the single lithium salt sealing process is in a wetted state (the water droplets are basically completely spread).
[0057] The adsorption capacity loss test was carried out on the once-sealed aluminum alloy test piece obtained by the single lithium salt sealing process in Comparative Example 1 (online direct blue ink dyeing test, drop amount: 1 drop, stay 1 minute), and the results are as follows Figure 3 As shown, (a) shows that after the blue ink is applied, the ink is wet and spread out; (b) shows that after the blue ink is washed with running water, the imprint remains obvious, indicating that the sealing of comparative example 1 is incomplete.
[0058] The once-sealed aluminum alloy test piece obtained in Comparative Example 1 was placed in the working solution of Example 5 for secondary sealing treatment, and the adsorption capacity loss test (online direct point blue ink dyeing test) was performed again on the obtained secondary sealed aluminum alloy test piece. The results are as follows: Figure 4 As shown in Figure (a), it can be seen that after the secondary sealing, the blue ink mark on the primary sealed aluminum alloy specimen is relatively Figure 3 (b) becomes lighter, indicating that the ink pigment molecules have seeped out, and the surface is hydrophobic when blue ink is applied again. As can be seen from Figure (b), no mark remains after the blue ink is washed with flowing water. Therefore, after the secondary sealing treatment of the present invention, the sealing quality can be effectively improved.
[0059] Comparative Example 2 The only difference from Example 4 is that no succinic acid is added to the secondary self-assembled hydrophobic membrane sealed concentrated solution, that is, the secondary self-assembled hydrophobic membrane sealed concentrated solution specifically includes: 2.5% sodium methylene bis naphthalene disulfonate, 1.5% sodium dodecylbenzene sulfonate, 5% magnesium sulfate, and the balance is pure water; the other steps and conditions are the same as those in Example 4.
[0060] Comparative Example 3 The only difference from Example 6 is that no FMEE penetrant is added to the secondary self-assembled hydrophobic membrane sealing concentrate; the other steps and conditions are the same as those in Example 6.
[0061] Comparative Example 4 The only difference from Example 7 is that the pH value of the working solution of the secondary sealing treatment is adjusted to 8.5 with 5% dilute ammonia water; the other steps and conditions are the same as those of Example 7.
[0062] Comparative Example 5 The only difference from Example 7 is that the pH value of the working solution of the secondary sealing treatment is adjusted to 3.5 with 2% glacial acetic acid; the other steps and conditions are the same as those of Example 7.
[0063] Comparative Example 6 A commercially available room temperature lithium salt sealer (a nickel-free room temperature lithium salt sealer code-named FT-F002H produced by Jiangsu Feituo Interface Engineering Technology Co., Ltd., including liquid agent A and solid agent B) was used as comparative example 6. The aluminum anodized film sample was sealed once according to the optimal process conditions, which were: 3.0% liquid agent A, 0.25% solid agent B in the tank. The temperature was controlled at 28°C, pH 8.6, and the time was 12 minutes.
[0064] Comparative Example 7 The aluminum anodized film sample was sealed once with a commercially available nickel fluoride room temperature sealer (room temperature nickel sealer LSF-86 produced by Wuhan Materials Protection Research Institute Co., Ltd., China Machinery General Academy) as comparative example 7. The process conditions were: 5g / L preparation tank, pH controlled at 5.8, time 8min, temperature 26°C.
[0065] Performance Testing The sealing quality is tested by the quick test method commonly used on the oxidation line, that is, the pure blue ink staining method is used immediately after the oxidation material is dry. The arbitration test is also conducted by the phosphochromic acid weight loss method of nitric acid pre-immersion according to the relevant national standard GB / T8753.1-2017. The appearance quality after sealing is visually inspected simultaneously.
[0066] The sealing results of the samples of each embodiment and comparative example are shown in Table 1, including the weight loss data of phosphochromic acid pre-soaked with nitric acid, adsorption capacity loss detection (online direct point blue ink dyeing detection), and apparent quality (including surface color, presence of sealing ash, smoothness of hand feel, stickiness, surface hydrophobicity and other characteristics). All weight loss data results are data after aging for 72 hours at room temperature of about 30°C.
[0067] Table 1 Sealing results of samples of various embodiments and comparative examples
[0068] It can be seen from Table 1 that after the secondary self-assembly sealing, the weight loss of the anodic oxide film sealing is from 60 to 70 mg / dm 2 (Comparative Examples 1 and 4) decreased to 30 mg / dm 2 The results are within the qualified line (Examples 1-7), close to the weight loss of the sealing at room temperature containing nickel salt (Comparative Example 7), and the sealing quality is significantly improved.
[0069] Not adding a small amount of fatty alcohol or derivatives has a greater impact on the self-assembly closure (Comparative Examples 2 and 3). After secondary closure, the weight loss exceeds 30 mg / dm2 , the stain test also has slight ink marks, but it feels smooth and not sticky.
[0070] pH has a great influence on the adsorption of self-assembled membranes. When the pH is above alkaline 8 (Comparative Example 4), the assembly and closure of the secondary membrane basically does not occur. There is no hydrophobic phenomenon of assembled membranes on the surface, indicating that self-assembly and closure of organic membranes basically do not occur. When the pH is too acidic (Comparative Example 5), the self-assembled membrane is formed normally on the surface, but the sealing effect of the original lithium salt is affected. The weight loss result of the arbitration test is significantly increased (unqualified), but the surface feels non-sticky.
[0071] In summary, the present invention provides a secondary self-assembled hydrophobic film sealing concentrate for aluminum anodized film and a sealing method. The concentrated solution is used as the raw material for the subsequent second sealing solution. It is a room temperature sealing solution that can form a hydrophobic sealing film again on the anodized film after the first lithium salt sealing, which can improve the sealing quality of the oxide film, and improve the sealing degree and pollution resistance of the anodized film; the surface after the secondary organic self-assembled hydrophobic film sealing has hydrophobic properties, and the pollution resistance is greatly improved, and the hand feel is smoother and non-sticky. Compared with the primary lithium salt sealing, the apparent quality and sealing quality are improved. The nitric acid pre-immersion weight loss test can stably meet the national standard requirements below 30°C (according to the national standard nitric acid pre-immersion phosphorus-chromic acid weight loss data detection reaches the national standard 30mg / dm 2 Compared with the closed surface of nickel at room temperature, the surface is uniform in color, smooth to the touch, and has an advantage in apparent quality; the present invention can effectively improve the closed surface state of the anodized film, and the online point blue ink adsorption capacity loss detection is completely free of pollution marks, making the surface of the oxide film uniformly hydrophobic, free of closed ash and smooth to the touch, and the lithium salt sealing can be carried out at room temperature (25-30°C), which is conducive to industrial production.
[0072] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A secondary self-assembled hydrophobic film enclosed concentrated solution of anodized aluminum film, characterized in that: Calculated by mass percentage, it includes the following components: 1% to 5% of sulfonate anionic surfactant, 0.1% to 0.5% of sealing accelerator, 2% to 6% of inorganic salt, 0 to 0.03% of bactericide, 0 to 0.05% of defoaming agent, and the balance is pure water.
2. The aluminum anodized film secondary self-assembled hydrophobic film closed concentrated solution according to claim 1, characterized in that: The sulfonate anionic surfactant includes C 10 ~C 16 Alkyl sulfonate, C 10 ~C 16 Alkylbenzene sulfonate, C 10 ~C 16 One or more of alkyl diphenyl ether disulfonates, methylene bis naphthalene disulfonates, α-olefin sulfonates, petroleum sulfonates, lignin sulfonates and naphthalenesulfonic acid formaldehyde condensates.
3. The aluminum anodized film secondary self-assembled hydrophobic film enclosed concentrated solution according to claim 2, characterized in that: The sulfonate anionic surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, sodium methylene dinaphthalene disulfonate, sodium lignin sulfonate, potassium lignin sulfonate and naphthalenesulfonic acid formaldehyde condensate.
4. The aluminum anodized film secondary self-assembled hydrophobic film closed concentrated solution according to claim 1, characterized in that: The blocking promoter includes one or more of C4-C8 fatty alcohol, C4-C8 fatty acid, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, and polyoxyethylene sorbitan fatty acid ester.
5. The aluminum anodized film secondary self-assembled hydrophobic film closed concentrated solution according to claim 4, characterized in that: The blocking promoter includes one or more of butanol, amyl alcohol, isoamyl alcohol, octanol, succinic acid, adipic acid, JFC penetrant, FMEE penetrant, Tween 20, Tween 40 and Tween 60.
6. The aluminum anodized film secondary self-assembled hydrophobic film closed concentrated solution according to claim 1, characterized in that: The inorganic salts include one or more of water-soluble salts of sodium, potassium, lithium, magnesium and calcium.
7. The aluminum anodized film secondary self-assembled hydrophobic film enclosed concentrated solution according to claim 1, characterized in that: The bactericide comprises a fatty amine polyoxyethylene ether surfactant, and the defoamer is a polyether defoamer.
8. A secondary sealing method for anodized aluminum film, characterized in that: The following steps are involved: Dilute the secondary self-assembled hydrophobic membrane sealing concentrated solution as described in any one of claims 1 to 7 with water and adjust the pH value to 4 to 7 to obtain a working solution; The aluminum anodized film sample was cleaned after being treated with nickel-free sealing to obtain a primary sealed sample; The primary sealing sample is immersed in the working solution, and then subjected to secondary sealing treatment. Finally, the secondary sealing of the aluminum anodized film is completed through drying.
9. The secondary sealing method of aluminum anodized film according to claim 8, characterized in that: The nickel-free sealing treatment is carried out by immersing the aluminum anodized film sample in a lithium salt sealing agent, the sealing temperature is 25°C to 30°C, and the sealing speed is 1.5 to 2 min / μm; the components of the lithium salt sealing agent include: 0.6 to 1.1 g / L of lithium ions, 0.3 to 0.6 g / L of fluoride ions, 0.5 to 1 g / L of tungstate, and the pH value of the lithium salt sealing agent is 8.5 to 9.0; cleaning includes water washing and pure water washing with a conductivity of less than 20 μs / cm.
10. The secondary sealing method of aluminum anodized film according to claim 8, characterized in that: The working solution is obtained by mixing and diluting the secondary self-assembled hydrophobic membrane sealing concentrate and pure water at a mass ratio of 1: (8-10) and adjusting the pH value to 4.5-5.5; The secondary sealing treatment is a soaking treatment at 22°C to 30°C for 5 to 15 minutes.